Maternal Diabetes Mellitus and Risk of Congenital Heart Defects in Offspring: A Cohort Study - Rubina Jabeen, Syeda Tasneem Kausar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess whether maternal diabetes mellitus (MDM) is associated with an increased risk of congenital heart defects (CHD) in offspring. Research design and methods: A population based cohort study was conducted by using information from the National Health Services and long term care of Punjab (Pakistan) health care administrative databases. The researcher identified all women with a MDM diagnosis with a live birth singleton delivery between June 2020 and May 2022. MDM was defined based on laboratory test results and diagnosis coding. Results: A total of 17,335 people with CHD remained allocated to embryologically relevant heart phenotypes. CHD recurrence was 328 per 11,500 live births (n=236) in offspring of women having gestational diabetes mellitus, associated to a baseline danger of 81 per 11,500; attuned comparative danger for CHD remained 5.01 (96 percent confidence range, 4.52–5.54). The connection was unaffected by birth year, maternal age at diabetes beginning, or diabetes extent, in addition CHD dangers associated with type 1 and DM type-2 were not substantially different. Individuals born to females who had previously experienced acute exacerbations had a higher risk of CHD than just those born to women who had not previously experienced acute diabetes complications (hazard ratio, 8.63; 96 percent confidence interval, 6.24–11.7, and relative risk, 4.48; 96 percent confidence interval, 3.92–5.14, respectively; P=0.0005). Maternal gestational DM remained related to all particular CHD phenotypes (adjusted hazard range, 3.75–15.9). Conclusion: In a large observational study, MDM was associated with an increased risk of CHD. Therefore, diabetes screening during pregnancy is suggested to identify women at risk for CHD.